(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Skin diseases encompass a broad spectrum, ranging from infectious and inflammatory conditions to severe neoplastic disorders. Traditional treatments, including antibiotics and corticosteroids, often present limitations such as adverse effects and resistance. Consequently, herbal remedies have emerged as safer, more sustainable alternatives. This study explores the therapeutic potential of Rubia cordifolia root extract in the management of skin diseases, focusing on its phytochemical composition, antimicrobial properties, and application in a gel formulation. The gel was evaluated for stability, spreadability, and efficacy through in vitro and clinical trials. Results demonstrated significant improvements in parameters such as pH stability, drug release, and patient-reported outcomes, including a 52.05% reduction in Psoriasis Area and Severity Index (PASI) scores. The study highlights the synergistic effects of combining herbal and conventional therapies, emphasizing the need for further research to establish Rubia cordifolia as a viable, cost-effective treatment for skin conditions.